Two-round relay selection and joint massive MIMO transmission technique to enhance wireless information and power transfer - Oussama, Messadi (2021)
Wireless Information and Power Transfer (WIPT) technology has recently drawn a great deal of interest. Its ability to convey both data and energy wirelessly to the user terminals prompted her to be a key technology to power the next generation of green wireless communications. However, given the high attenuation of radiofrequency signals across distance on the one hand and the Federal Communications Commission (FCC) rules and regulations regarding safety issues and determining the maximum transmission power, makes the implementation of WIPT poses serious challenges. Over and above, the integration of WIPT with other emerging technologies, i.e., Massive multiple-input, multiple-output (MIMO) system and multi-antenna beamforming technique, raises the need to design new schemes and system architectures to achieve effective integrations. This thesis aims to improve the amount of energy harvested and enhance the system of WIPT by implementing an effective integration with massive MIMO and wireless powered cooperative communication networks (WPCCNs). In the first part of the thesis, we focus on enhancing the throughput and analysing the outage performance of a new WPCCNs system model, where both the single source and the multi-relay have no fixed energy supply. A power-beacon is proposed in the network to assist the source and relays harvest energy from their radio frequency (RF) signals. Two partial relay selection schemes (PRS) and opportunistic relay selection scheme (ORS) are implemented and analysed for the proposed system model, where the best relay selection is picked based on the channel state information availability. The outage probability and the system throughput mathematic equations over different relay selection schemes are derived and confirmed with Monte-Carlo simulations. The numerical results have shown that the performance of ORS relay selection scheme over the two PRS selection schemes in terms of system throughput by 39% compared to PRSII and 19% compared to PRSI. The impact of multi-relay number and the harvesting time is also investigated. The second part of the thesis addresses another WIPT research challenge from a network-level perspective. In WIPT and in addition to the reception reliability, the amount of harvested power is important as well in the best relay selection process. Thus, in WIPT, the max-min selection criterion is not optimal since the best energy harvesting relay does not always correspond to the best relay for information transmission. A new relay selection scheme suitable for WIPT architectures referred to as two round relay selection scheme (2-RRS) is proposed and analysed. The proposed 2-RRS scheme is compared with the conventional ORS and PRS schemes. The closed-form expression for the outage probability and the throughput performance of the proposed 2-RRS scheme and the conventional PRS and ORS schemes are derived. Numerical simulations validated the theoretical results, where the system throughput with the new proposed 2-RRS scheme is enhanced by {15%,37%,62%} comparing to ORS, PRSI and PRSII schemes, respectively, when the PB parameters are PPB = 10dB and M = 64. The optimal energy harvesting time values are obtained by an exhaustive search for each relay selection scheme. The impact of the number of antennas and relays on the throughput performance is studied. The best PB position for each relay selection is investigated based on the selection criteria. In the third part of the thesis, two new transmission techniques that enable massive- MIMO and simultaneous wireless information and power transfer (SWIPT) systems integration were proposed analysed and compared. In particular, in the first technique, the BS transfers data to a scheduled group of users (S-terminals) and takes advantage of the channel matrix’s null space for these scheduled users to transmit power to non-scheduled users (N-terminals) at the same time-frequency resource. This technique is referred to as joint beamforming and broadcasting SWIPT (JBBSWIPT). The second technique is orthogonal beamforming and broadcasting SWIPT (OBB-SWIPT), where the downlink time-frequency resources are divided into two separate parts: one for beamforming information to the S-terminals, and the second part for broadcasting energy to the non-scheduled N-terminals which their CSI is not available at the BS. The closed-form expressions for the S-terminals average achievable data rate, and the N-terminals average harvested power are derived and compared for both proposed JBB-SWIPT and OBB-SWIPT, respectively. The amount of harvested energy by the proposed JBB-SWIPT reach up to three times the amount of harvested energy by OBB-SWIPT when the number of S-terminals are close to the number of BS antennas.